Contrasting the Treatment-Related Perceptions of Parents and Their Children: Using Data from Child and Adolescent Brief Mental Health Services Recipients in Canada - Ellenbogen, Stephen; B. Power, Keith; J. Hair, Heather; Kirkland Smith, June; Hynes Brothers, Kristen (European Journal of Mental Health, 2024)
Introduction: Discrepancies between parental and child perceptions of problems and their therapeutic expectations can negatively impact mental health treatment efficacy. Aims: We sought to explore concordance and discrepancy in families receiving brief, client-centered, and strengths-based mental health services, specifically by contrasting parents’ and children’s perceptions of the child’s presenting issues; treatment expectations; and levels of concern pre- and post-treatment. We also examined the psychometric properties of a therapeutic scaling question on the level of concern, by examining associations with scores from the Strengths and Difficulties Questionnaire. Methods: Using a mixed-methods approach, we examined data from openand closed-ended questions, some used as part of the treatment. This included brief descriptions of perceived presenting issues and treatment expectations, and levels of concern on a scale of 1 to 10. Results: Parent and child descriptions of issues were judged generally congruent 66% of the time. Respectively, minor and major non-congruence was observed 25% and 9% of the time. In terms of treatment expectations, parents were more likely to express a desire to understand the issues and improve communication in the family. Children were more likely to express no expectancies or respond with simple statements (e.g., feel better). Parents initially rated their children’s problems as more severe than did their children. We found that the scaling question demonstrated a modest association with the level of concern from the Strength and Difficulties Questionnaire (SDQ). Conclusions: Even though most parents and their children broadly agree on presenting mental health issues for which they seek counseling, important differences manifest in how they perceive them and what they want accomplished during sessions. Practitioners need to consider, assess, and accommodate such discrepancies.